VD_FINDINFO HC / 2013 / 42 vom 18. Januar 2013 - VD Tribunal cantonal (2013)
ADMINISTRATION D'OFFICE DE LA SUCCESSION, EXÉCUTEUR TESTAMENTAIRE, JURIDICTION GRACIEUSE | 554 al. 2 CC, 554 CC, 321 CPC (CH), 109 al. 3 CDPJ